2022
DOI: 10.3389/fpls.2022.873471
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability in Balkan Paleoendemic Resurrection Plants Ramonda serbica and R. nathaliae Across Their Range and in the Zone of Sympatry

Abstract: The genus Ramonda includes three Paleoendemic and Tertiary relict species that survived in refugial habitats of the Balkan Peninsula (R. nathaliae and R. serbica) and the Iberian Peninsula (R. myconi). They are all “resurrection plants,” a rare phenomenon among flowering plants in Europe. Ramonda myconi and R. nathaliae are diploids (2n = 2x = 48), while R. serbica is a hexaploid (2n = 6x = 144). The two Balkan species occur in sympatry in only two localities in eastern Serbia, where tetraploid potential hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
(139 reference statements)
0
3
0
Order By: Relevance
“…Backcrossing with one or both parental species can result in individuals that are morphologically difficult to distinguish from the parent species, making the identification of hybrids based on morphology challenging or impossible. This phenomenon has already been observed in numerous plant genera, including Cardamine [ 39 ], Betula [ 35 ], Pinus [ 32 , 34 ], Knautia [ 40 ], Primula [ 41 ], Ruppia [ 42 ], Ramonda [ 43 ], etc.…”
Section: Discussionmentioning
confidence: 78%
“…Backcrossing with one or both parental species can result in individuals that are morphologically difficult to distinguish from the parent species, making the identification of hybrids based on morphology challenging or impossible. This phenomenon has already been observed in numerous plant genera, including Cardamine [ 39 ], Betula [ 35 ], Pinus [ 32 , 34 ], Knautia [ 40 ], Primula [ 41 ], Ruppia [ 42 ], Ramonda [ 43 ], etc.…”
Section: Discussionmentioning
confidence: 78%
“…However, as noted by these authors, this should not inhibit the detection of hybridizations. Numerous studies have confirmed the power of AFLP markers in detecting interspecific hybridization (e.g., [23,24,[37][38][39]). Altogether, the 1022 loci produced in this study allowed a powerful discrimination between the studied species and the identification of several individuals that could be considered as progenies of interspecific hybridization.…”
Section: Discussionmentioning
confidence: 96%
“…The variation in the GS among species is widely documented, particularly in plants [ 30 ], and its impacts play a key role in plant biodiversity, ecology and evolution [ 30 , 39 , 52 , 53 , 54 , 55 , 56 ]. There are also several reports on the relationship between the intraspecific variation in the GS and the phenotypic, phenological or ecological factors [ 28 , 31 , 34 , 57 , 58 , 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%